39.72-7.6n=0.8(n-6)

Simple and best practice solution for 39.72-7.6n=0.8(n-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 39.72-7.6n=0.8(n-6) equation:



39.72-7.6n=0.8(n-6)
We move all terms to the left:
39.72-7.6n-(0.8(n-6))=0
We calculate terms in parentheses: -(0.8(n-6)), so:
0.8(n-6)
We multiply parentheses
0.8n-4.8
Back to the equation:
-(0.8n-4.8)
We get rid of parentheses
-7.6n-0.8n+4.8+39.72=0
We add all the numbers together, and all the variables
-8.4n+44.52=0
We move all terms containing n to the left, all other terms to the right
-8.4n=-44.52
n=-44.52/-8.4
n=5+1/3.3333333333333

See similar equations:

| -6-7=-7f | | 3(-7+4r)=-93 | | (2x+9)*2=3x+35 | | 2p-9=-7p | | (3x+35)/2=(2x+9) | | -8(-3x+6)=-120 | | v+1/5=13/5+7v | | -d=8-2d | | -8-8m=-6m | | h−12=54 | | -4^3+84^2+432x+250=0 | | f+4/2=10 | | -8(3+7x)=200 | | (2x+9)=(3x+35)/2 | | -2-n=-5-2n | | s+13.5=17 | | 7v+2(7v-2)=-172 | | -20−20+11n=20+14n | | -6p=-3p-3 | | 142+83x=30-x | | 9u=-3=8u | | -5n=4-4n | | -254=-6(1-5p)+p | | -7q=10-9q | | 5(k-2)=(3k-9) | | k2− 1=1 | | 1/2=1/2.x+3 | | 41=-6(-3a+2)+5(1+6a) | | 7x−4+x=−1+13x+7 | | -105=7(1-2x) | | -6j=-4-10j | | 2(4-4x)=7x+14-2x |

Equations solver categories